Cross-reactivity of Malaysian rat cytomegalovirus strains with its human counterpart - Camalxaman, Siti Nazrina; Allaudin, Zeenathul Nazariah; Quah, Yi Wan; Loh, Hwei San; Hassan, Zuridah; Abdul Rahman, Sheikh Omar; Mohd Lila, Mohd Azmi (Malaysian Society of Parasitology and Tropical Medicine, 2011)
This study probes into the prospect of cross-reactivity of HCMV with RCMV which has not been acknowledged to date. We describe the uncovering of a protein with an estimated size of between 61-68 kDa from local RCMV strains which reacted with HCMV positive sera. Our findings are a first disclosure of a plausible immunological cross-reactivity between RCMV with its human counterpart which grounds substantial interest implying existence of conserved determinants between rat and human CMV polypeptides. The cross-reactive protein most likely represents an enveloped glycoprotein, though the precise identification and its degree of similarity needs to be evidently defined and further elucidated in forthcoming experiments.